Utilization of Indocyanine Green (ICG) Fluorescence in Patients with Pediatric Colorectal Diseases: The Current Applications and Reported Outcomes - Elizaveta Bokova; Ismael Elhalaby; Seth Saylors; Irene Isabel P. Lim; Rebecca M. Rentea (MDPI AG, 2024)
In pediatric colorectal surgery, achieving and visualizing adequate perfusion during complex reconstructive procedures are paramount to ensure postoperative success. However, intraoperative identification of proper perfusion remains a challeng. This review synthesizes findings from the literature spanning from January 2010 to March 2024, sourced from Medline/PubMed, EMBASE, and other databases, to evaluate the role of indocyanine green (ICG) fluorescence imaging in enhancing surgical outcomes. Specifically, it explores the use of ICG in surgeries related to Hirschsprung disease, anorectal malformations, cloacal reconstructions, vaginal agenesis, bladder augmentation, and the construction of antegrade continence channels. Preliminary evidence suggests that ICG fluorescence significantly aids in intraoperative decision-making by improving the visualization of vascular networks and assessing tissue perfusion. Despite the limited number of studies, initial findings indicate that ICG may offer advantages over traditional clinical assessments for intestinal perfusion. Its application has demonstrated a promising safety profile in pediatric patients, underscoring the need for larger, prospective studies to validate these observations, quantify benefits, and further assess its impact on clinical outcomes. The potential of ICG to enhance pediatric colorectal surgery by providing real-time, accurate perfusion data could significantly improve surgical precision and patient recovery.